A local flour - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Developed in Burkina Faso in 1992 by a French NGO, Misola flour is an infant food made from locally cultivated cereals and legumes (millet, soya and peanut).